2020
DOI: 10.1021/acs.iecr.0c01415
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive Separation of Furfural/5-Hydroxymethylfurfural in MAF-5 with Ellipsoidal Pores

Abstract: The objective of this work is to study the adsorptive separation of the biomass-derived furfural (Fur) and 5-hydroxymethylfurfural (5-HMF). Because Fur and 5-HMF have similar ellipsoidal shapes, the diffusion of the larger 5-HMF may be blocked by the elliptical window of adsorbents. Thus, two zeolitic imidazolate framework (ZIF) materials with the identical chemical composition, MAF-6 and MAF-5, were used as spherical and ellipsoidal pore adsorbents, respectively. In the dynamic column adsorption of a binary-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 40 publications
0
7
0
7
Order By: Relevance
“…The adsorption selectivity ( S ) of component i was calculated by Eqn (2). 17 S=Qads,i/C0,iQads,j/C0,j …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The adsorption selectivity ( S ) of component i was calculated by Eqn (2). 17 S=Qads,i/C0,iQads,j/C0,j …”
Section: Methodsmentioning
confidence: 99%
“…Zeolitic imidazolate frameworks (ZIFs)-derived porous carbon (C) materials are highly promising candidates when compared to previously reported adsorbents, including activated C, [6][7][8][9][10] polymers [11][12][13] and ZIFs. [14][15][16][17] The excellent adsorption behavior lies in the tunable surface chemistry/pore structure of C and its π-π interactions with furfural. 18 Our recent study demonstrated that furfural adsorption is closely related to the hydrophobicity, electrostatic interactions and π-π interactions of the adsorbent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adsorbents are promising materials for capturing pollutants, such as low-molecular organics and heavy metal ions, because of their abundant sorption sites, large surface area, and fast adsorption kinetics [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. However, adsorbents are usually synthesized in the form of powders, which give rise to some problems in the separation and regeneration processes [ 15 , 16 ] and potential safety issues may occur due to leaching into water bodies [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, 5-HMF can be further rehydrated into byproducts under acidic conditions, such as LA, FA, and humins, , which results in great difficulty to separate and purify 5-HMF from such diluted and complex multicomponent systems . In the last two decades, considerable efforts have been devoted to the selection and optimization of the catalyst systems to enhance C6 sugar conversion as well as 5-HMF yields. However, only a few investigations have been focusing on the separation of 5-HMF from such dilute aqueous solutions or hydrolysates. Separation and recovery of 5-HMF by distillation not only requires high energy consumption but also leads to a great risk of polymerization of 5-HMF due to instability at high temperature. Vinke and Bekkum first presented selectively recovered 5-HMF from aqueous mixtures with fructose and LA using three activated carbons in terms of R0.8 A, ROX 0.8, and C-granular.…”
Section: Introductionmentioning
confidence: 99%